2020
DOI: 10.1109/access.2020.2992631
|View full text |Cite
|
Sign up to set email alerts
|

An Approach of One-vs-Rest Filter Bank Common Spatial Pattern and Spiking Neural Networks for Multiple Motor Imagery Decoding

Abstract: Motor imagery (MI) is a typical BCI paradigm and has been widely applied into many aspects (e.g. brain-driven wheelchair and motor function rehabilitation training). Although significant achievements have been achieved, multiple motor imagery decoding is still unsatisfactory. To deal with this challenging issue, firstly, a segment of electroencephalogram was extracted and preprocessed. Secondly, we applied a filter bank common spatial pattern (FBCSP) with one-vs-rest (OVR) strategy to extract the spatio-tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Sakhavi et al [15] utilized a FBCSP to generate temporal representations of EEG which were then fed into a CNN for the EEG classification. In addition, the spiking neural network was used [16] and combined with OVR (One-Vs-Rest) FBCSP which extracted temporal-frequency features from multiple MI-EEG. Li et al [14] further investigated multi-domain representation of EEG and performed spectral and temporal analysis together with a designed CNN.…”
Section: He Brain Computer Interface (Bci) Creatively Provides New Ways For Communication Between Human and Computers Bymentioning
confidence: 99%
“…Sakhavi et al [15] utilized a FBCSP to generate temporal representations of EEG which were then fed into a CNN for the EEG classification. In addition, the spiking neural network was used [16] and combined with OVR (One-Vs-Rest) FBCSP which extracted temporal-frequency features from multiple MI-EEG. Li et al [14] further investigated multi-domain representation of EEG and performed spectral and temporal analysis together with a designed CNN.…”
Section: He Brain Computer Interface (Bci) Creatively Provides New Ways For Communication Between Human and Computers Bymentioning
confidence: 99%
“…The selection of the time window can remove the segmentation of EEG signals that have nothing to do with MI or eliminate data that is not the key time point of MI [27]. Our previous study has also shown that choosing the optimal time window for each subject can indeed improve the classification accuracy [40]. Although the optimal time windows of each subject's MI are different, it is found that the time between 0-2.5 s after the onset of visual cue can benefit the classification considering adequate sample points for subsequent data processing [41].…”
Section: A Time Window Selectionmentioning
confidence: 99%
“…In the following years, several variations/modifications of the original algorithm were proposed (e.g. [23]- [26]) that led to This work is licensed under a Creative Commons Attribution 4.0 License. For more information, see https://creativecommons.org/licenses/by/4.0/ more robust MI-decoding schemes.…”
Section: Introductionmentioning
confidence: 99%